Kinerja Penyuluh Pertanian dalam Pelaksanaan Program Komando Strategis Pembangunan Pertanian (Kostratani) di Kabupaten Sragen - Tika Sekar Kinasih; Widiyanto Widiyanto; Suminah Suminah (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2022)
The Kostratani program is one of the agricultural development activities at the sub-district level. This research aims to analyze the factors that affect the performane of agricultural extension in the implementation of the Kostratani program in Sragen Regency. The subjects o this research are all agricultural extension in Sragen Regency who are civil servants as many as 54 peoples, the determination of research subjects was carried out by the census method. This research uses quantitative methods with survey techniques. Data analysis by using descriptive analysis and multiple linear regression test. The result of the analysis shows that the performance of agricultural extension in Sragen Regency for implementation Kostratani program is in the good enough category. The factors have a significant affect on the performance of agricultural extension in Sragen Regency by 19,5% at the level of significance α=5%. Keyword: Agricultural Extension, Performance, Kostratani